The Role Of Inter-Sectors In Agroforestry Development In The Community Forest Environment, Pacitan District - Anang Susanto; Marti Winarni Susanto (International Journal of Science and Environment (IJSE), 2023)
Communities around the forest need to be encouraged in the development of forestry plants by the community either independently or with the assistance—of the government so that environmental sustainability can be adequately controlled. The development system carried out by the community, in general, is a hybrid system or better known as the agroforestry system. This study aims to identify sectors related to efforts to develop forestry plants.airly well-established economic condition. Development of forestry plants with this system . However, few people also develop a monoculture system, especially those with large enough land and who do not depend on the ground. Building role synergy between sectors supporting the development of forestry plantations is urgently needed to increase the quantity and quality of raw materials to meet the needs of the timber industry, both locally and nationally. Three critical sectors that must synergize in supporting the development of forestry plantations by the community are research and educational institutions, the government, and the market (industry). These three sectors are expected to be able to build attractive incentives for the community so that the community continues to preserve timber plants. Research and educational institutions can provide information and technology related to efforts to increase forestry plant production. Both information and technology from social, economic, and silvicultural or cultivation aspects. Information and technology produced by these research and educational institutions can be used as input and consideration for the government in formulating programs and policies related to developing timber plantations on private land. Through the formulation of its policies and work programs, the government is expected to initiate, facilitate and assist the community in developing forestry plants. Furthermore, the market sector, especially the timber industry, must be encouraged to create a conducive post-harvest climate so that the community continues to be motivated to increase the production of raw wood materials.